O ciberespaço e a predação sexual infanto-juvenil: uma revisão da literatura. - Alves, Barbara Lorena e Sila (2023)
Despite being vectors of progress, Information and Communication Technologies (ICTs) contribute to the dissemination and amplification of violence. Among the numerous challenges, there is an aspect to be considered, which relates to the expansion of child and adolescent sexual predation and the need to understand and analyze the functioning of these predators who find a favorable field for their expression in cyberspace. It is necessary to further explore the subject, as well as actions that bring visibility to the different characteristics of this specific type of violence. Based on these aspects, the present study aims to raise awareness of and understand the various forms of child and adolescent sexual predation in cyberspace. The specific objectives are as follows: (I) conduct a narrative literature review on the topic using national and international databases; (II) understand the use of the internet by children and adolescents; (III) produce knowledge that contributes to the development of prevention strategies. To achieve these objectives, this dissertation will follow an exploratory research approach using a qualitative methodology, which will include a literature review based on previously published material, mainly books and articles available on the internet, to outline the state of the art. To conduct the literature review for this study, the most relevant scientific databases in the field of psychology, such as Google Scholar, PsycINFO, and Web of Science, were utilized. The following keywords were used in these databases: cybersexual predation, online sexual predation, cyberpedophilia, and online pedophilia. Additionally, Boolean operators were used in the databases Lilacs, Scielo, and Pubmed, with search filters for MeshTerms, Topic, and Keywords. Through searches conducted in various academic databases, it was possible to observe that cybersexual predation is a growing phenomenon that is related to a multisectoral problem, regulated by specific laws and regulations in each context/culture, which hinders the operationalization of this phenomenon in the Brazilian reality. There is a notable lack of studies on this violence in the Brazilian context. Based on the data collected, it is hoped to assist professionals from various fields (e.g., psychology, education, social work) in understanding the phenomenon, thus enabling further research investments in this area and providing greater knowledge on the subject in order to provide guidance for parents and guardians. Furthermore, as this is still a developing area in the national context, the research represents an innovative approach by seeking theoretical evidence for the field of Cyberpsychology, specifically regarding possible forms of prevention of child and adolescent cybersexual predation.